Five-Year Action Plan for Curriculum Development - Embree, Alan. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1975)
With the aid of a grant from the Advanced Institutional Development Program, a group of Central YMCA Community College (CYCC) faculty were given released time to inquire into curriculum priorities. This document establishes the focal points of future curriculum discussions and outlines the developments which this faculty group hopes will ensue as a result of their inquiry. A five-year action plan, based on other recent studies conducted at CYCC, is proposed for the orderly implementation of curriculum development, maintaining student welfare and educational experience as the primary target. Strengths and weaknesses of the present structure and possible means of improvement are noted in sections on student needs, special curricula for ethnic and social minority groups, interdepartmental and interdisciplinary programs, extension programs, flexible scheduling, support services, performance objectives, evaluation of instruction, alternative ways of earning credit, new programs, and course and material development. A hierarchy of priority issues to be confronted from spring 1975 through spring 1976, and the rationales for the selection of specific priorities are presented. New courses and material development are designated as continuing concerns to insure significant achievements for the entire curriculum and to provide the basis for other research. (AH)
Educational level discussed: Two Year Colleges.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Ancillary Services; Bilingual Education; College Credits; College Curriculum; Curriculum Development; Educational Objectives; Institutional Research; Material Development; Minority Groups; Nontraditional Education; Released Time; Teacher Evaluation; Teacher Participation; Two Year Colleges; Central YMCA Community College IL; Illinois; Reports, Research